Epidemiological characteristics of Omicron and Delta SARS-CoV-2 variant infection in Santiago, Chile - Mella-Torres, Andrea; Escobar, Alejandro; Barrera-Avalos, Carlos; Vargas-Salas, Sergio; Pirazzoli, Michelle; Gonzalez, Ulises; Valdes, Daniel; Rojas, Patricio; Luraschi, Roberto; Vallejos-Vidal, Eva; Imarai, Mónica; Sandino, Ana María; et al. (Frontiers in Public Health, 2022)
The variant of concern (VOC) SARS-CoV-2 Omicron (B.1.1529) has been described as a highly contagious variant but less virulent than the current variant being monitored (VBM) Delta (B.1.617.2), causing fewer cases of hospitalizations, symptomatology, and deaths associated with COVID-19 disease. Although the epidemiological comparison of both variants has been previously reported in other countries, no report indicates their behavior and severity of infection in Chile. In this work, we report for the first time the effect of the Omicron and Delta variants in a cohort of 588 patients from the Hospital de Urgencia Asistencia pública (HUAP), a high-complexity health center in Santiago, Chile. This report is framed at the beginning of Chile's third wave of the COVID-19 pandemic, with a marked increase in the Omicron variant and a decrease in the circulating Delta variant. Our results indicated a similar proportion of patients with a complete vaccination schedule for both variants. However, the Delta variant was associated with a higher prevalence of hospitalization and more significant symptomatology associated with respiratory distress. On the other hand, our data suggest that vaccination is less effective in preventing infection by the Omicron variant. This antecedent, with a low severity but high contagiousness, suggests that the Omicron variant could even collapse the primary health care service due to the high demand for health care.